A NEW SECTION OF BEGONIA (BEGONIACEAE) FROM WEST CENTRAL AFRICA - DE WILDE, J. J. F. E.; PLANA, V. (Edinburgh Journal of Botany, 2003)
Previous analyses of macromorphological and molecular data on the continental African species Begonia iucunda (Begoniaceae) suggest that it occupies an isolated phylogenetic position within a clade consisting otherwise of species in sections Cristasemen, Filicibegonia, Loasibegonia and Scutobegonia. Accordingly, the new monotypic section Chasmophila is here described. Its taxonomic position and relationship to other African sections are discussed and data on its distribution and ecology are presented.